Protein & Cell - Rao, Zihe
Protein & Cell publishes original research articles, reviews, and commentaries concerning the latest developments in multidisciplinary areas in biology and biomedicine, with an emphasis on protein and cell research. Our subject areas include, but are not limited to, biochemistry/biophysics, cell biology, developmental biology, genetics, immunology, microbiology, molecular biology, neuroscience, oncology, protein science, structural biology and translational medicine. In addition, Protein & Cell addresses research highlights, news and views, and commentaries covering research policies and funding trends in China, and seeks to provide a forum to foster academic exchange among researchers across different fields of the life sciences. Protein & Cell is a peer-reviewed open access journal published monthly. The open access fees (article-processing charges) for this journal are kindly sponsored by Higher Education Press, Beijing Institutes of Life Science, Chinese Academy of Sciences and Biophysical Society of China. Authors can publish in the journal without any additional charges.